Immobilization of Providencia stuartii Cells in Papaya Trunk Wood for N-acetylglucosamine Production from Pennaeus vannamei Shrimp Shells - Yuniwaty Halim; Steven Fausta Tantradjaja; Hardoko Hardoko; Ratna Handayani (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight Research AbstractChitin is a natural compound found abundantly in shrimp shells. Chitin can be degraded to produce N-acetylglucosamine, which has wide applications in the food and pharmaceutical fields. Fermentation using chitinolytic microorganisms can be used to produce N-acetylglucosamine from shrimp shells' chitin. One of the strong chitinolytic bacteria that was isolated from previous research was Providencia stuartii. To provide better stability and efficiency in fermentation, P. stuartii cells were immobilized using entrapment method in papaya trunk wood. The aims of this research were to determine the optimum papaya trunk wood size, ratio of papaya trunk wood and growth medium, as well as the optimum fermentation cycle to produce N-acetylglucosamine from P. vannamei shrimp shells using submerged fermentation method. The research used experimental method with treatment of different sizes of papaya trunk wood (1 x 1 x 1 cm3, 1.5 x 1.5 x 1.5 cm3, and 2 x 2 x 2 cm3), different ratio of papaya trunk wood and growth medium (1:10, 1:15 and 1:20), and 4 fermentation cycles. Results showed that papaya trunk wood with size of 1 x 1 x 1 cm3 and ratio (w/v) of 1:10 could immobilize 87.08±2.05% of P. stuartii cells and produce the highest N-acetylglucosamine concentration, which was 238177.78±3153.48 ppm. The highest N-acetylglucosamine production was obtained from first fermentation cycle and decreased over the last three cycles, but still produced high concentration of N-acetylglucosamine. Therefore, it is possible to perform continuous N-acetylglucosamine production from shrimp shells using P. stuartii cells immobilized in papaya trunk wood.